The influence of principals’ intellectual stimulation, digital literacy, and self-efficacy on teachers’ innovative behaviors - Noviyanti, Yenni; Irsyad; Rusdinal; Sulastri (Universitas Jambi, Indonesia, 2025)
This research employed a quantitative method to analyze the direct and indirect effects of principals' intellectual stimulation, digital literacy, and self-efficacy on teachers' innovative behavior. Data were collected from 85 public elementary school teachers in West Pasaman Regency through a questionnaire and analyzed using SEMPLS. The results indicated a direct positive effect of the principals' intellectual stimulation (5.8%), digital literacy (52.8%), and self-efficacy (26.7%) on teachers' innovative behavior. In addition, principals' intellectual stimulation (28.4%) and digital literacy (64.9%) also positively affected self-efficacy. The indirect pathway, through self-efficacy, showed that principals' intellectual stimulation contributed 7.6% to teachers' innovative behavior, and digital literacy contributed 17.3% indirectly. These findings confirm that the principals' intellectual stimulation, digital literacy, and self-efficacy are crucial factors that can encourage teachers' innovative behavior. The findings indicate that the principal’s intellectual stimulation, digital literacy, and self-efficacy are three factors that can influence teachers’ innovative behavior.